New Electroactive Polymers with Electronically Isolated 4,7-Diarylfluorene Chromophores as Positive Charge Transporting Layer Materials for OLEDs - Krucaite, Gintere; Tavgeniene, Daiva; Blazevicius, Dovydas; Zhang, Baohua; Vembris, Aivars; Grigalevicius, Saulius (MDPI, 2021)
A group of polyethers containing electroactive pendent 4,7-diarylfluorene chromophores have been prepared by the multi-step synthetic route. Full characterization of their structures has been presented. The polymeric materials represent derivatives of high thermal stability with initial thermal degradation temperatures in a range of 392–397 °C. Glass transition temperatures of the amorphous polymers range from 28 °C to 63 °C and depend on structures of the 4,7-diarylfluorene chromophores. Electron photoemission spectra of thin layers of the electroactive derivatives showed ionization potentials in the range of 5.8–6.0 eV. Hole injecting/transporting properties of the prepared polymeric materials were confirmed during formation of organic light-emitting diodes with tris(quinolin-8-olato)aluminium (Alq3) as a green emitter, which also serves as an electron transporting layer. The device using hole-transporting polymer with electronically isolated 2,7-di(4-biphenyl) fluorene chromophores demonstrated the best overall performance with low turn on voltage of 3 V, high current efficiency exceeding 1.7 cd/A, and with maximum brightness over 200 cd/m2. The organic light-emitting diode (OLED) characteristics were measured in non-optimized test devices. The efficiencies could be further improved by an optimization of device structure, formation conditions, and encapsulation of the devices..---//---This work is licensed under a CC BY 4.0 license.
The OLED materials were developed in the frame of project funded by the Research Council of Lithuania (grant No. S-LLT-19-2). B.Z. is thankful to the National Natural Science Foundation of China (No. 51773195), and the Research & Development Projects in Key Areas of Guangdong Province, China (No. 2019B010933001). We are also obliged to D. Volyniuk for measurements of the ionization potentials.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; polyether; ﬂuorene; hole transporting material; ionization potential; organic light emitting diode